Interrelasi Fundamentalisme dan Orientasi Ideologi Gerakan Islam Kontemporer - Ahmad Nur Fuad (Islamica: Jurnal Studi Keislaman, 2007)
This article deals with the interrelation between Islamic fundamentalism and other ideological orientations of contemporary Islamist movements, such as Islamism, revivalism, radicalism, salafism, and political Islam. It tries to explore the similarities in their characteristics as well as their differences in the focuses and strategies of the movements. This articles argues that these Islamist movements express their ideological aspirations in different ways: some try to build an Islamic state or even a universal Islamic caliphate (political Islam), while others emphasize much more on the implementation of shari?ah in the level of individuals and society, apart from state (salafis). However, they did not succeed yet in transforming the political landscape of the Muslim world in accordance with their ideological framework.